Kajian Pemanfaatan FWD Sebagai Alat Uji Struktur Perkerasan Jalan - I Ketut Darsana; Wawan Darmawan (Jurnal Jalan-Jembatan, 2005)
Since 1990s Research and Development Center for Road Infrastructure has had Falling Weight Deflectometer (FWD), is one of the equipment to test road pavement structure completed by computerize system in measuring accuracy and speed. However, the evaluation on this equipment has not yet done. Therefore, it should be carried out a study on FWD to know how the usage of FWD technically and economically suits to management principles. FWD capacity reaches 251,280 points < 404,000 points (Dynatest-8002). Technically FWD has not optimatised yet in its capacity but its operation has been suitable to management procedures. Due to limitation on cooperation and services of FWD, its capacity can be increased until 40,000 points per-year to maximaze the provits or to increased with the payment from Rp 25,000,- to Rp 36,000 for one-point if minimize the losses. The choice of the as above alternative should be evaluated to get maximum result beside considering it as the main usage of FWD for research services; while FWD capacity is used to give services to other needed parties.